Pemikiran Hukum Gerakan Islam Radikal Studi atas Pemikiran Hukum dan Potensi Konflik Sosial Keagamaan Majelis Mujâhidin Indonesia (MMI) dan Jamâ’ah Anshârut Tauh?id (JAT - Moh. Dliya'ul Chaq (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2013)
MMI and JAT as a radical Islamic movement that carries the purification of religious doctrine, including the harmonization rejection of Islam and culture are interesting facts especially when ideology was living in Indonesia and dealing with the fact mainstream Indonesian Muslim religious dynamics of Islam that emphasizes the Indonesian culture. Sociology approach religion with models interactive content analysis with literature data and found the results of the study. First, the failure of non-Islamic system to overcome the problem of the Indonesian nation since independence is the background of the founding of MMI and JAT. Second, MMI and JAT have legal thought in the form of source of Islamic law is the Qur'an and hadith, the obligations enforce of shari'at Islam in the form of an Islamic state or khilafah Islamiyah, and the duty of jihad. Third, the idea of law has the potential social conflict and violence in Indonesia as opposed to mainstream legal thought muslim in Indonesia.